The Extended Rights to Purchase Policy : Reduction of Blackout Periods in GRA Arrangements. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2013)
This note provides guidance on the operation of the IMF's Extended Rights to Purchase policy for General Resources Account (GRA) arrangements. Provided certain safeguards are met, this policy extends the period (up to some limits) in which a member may access accumulated but undrawn balances under a GRA arrangement once a new test date is reached but for which the test data are not yet available. In so doing it addresses some access 'blackouts' which can affect all GRA arrangements with the Fund, but especially precautionary ones. To assist in program design, other possible access blackouts, not addressed by this policy, are also described in this note.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet